REVITALIZING NUTRIENT-DENSE MILLET-AMARANTH WAFFLE SANDWICH WITH PROBIOTIC-INFUSED CREAM- A COMPREHENSIVE FUNCTIONAL FOODS ANALYSIS (International Journal of Food and Nutritional Sciences, 2025)
Abstract: This research paper investigates the development of a nutritious breakfast option using millet (Ragi), amaranth (Rajgira), and probiotic-infused cream in waffle formulation. Emphasizing their high protein, fiber, and micronutrient content, the study optimizes sensory attributes. Chemical analyses encompass pH and acidity assessments, while biochemical evaluations include gram staining and catalase tests. Despite challenges in achieving diverse probiotic strains, the study underscores the product's potential as a health-promoting breakfast, integrating traditional grains with functional ingredients.